2001
DOI: 10.1074/jbc.m004972200
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of the Stem Region as a Functional Domain Responsible for the Oligomerization and Golgi Localization of N-Acetylglucosaminyltransferase V

Abstract: We demonstrated that a region in the stem of N-acetylglucosaminyltransferase V (GnT-V), a Golgi resident protein, is not required for enzyme activity but serves as functional domain, responsible for intracellular localization. Deletion of the domain led to complete retention of the kinetic properties but resulted in the cell surface localization of the enzyme as well as its efficient secretion into the medium. The lack of this domain concomitantly abolished the disulfide-mediated oligomerization of GnT-V, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…Similar results have been reported for GnT-V, a Golgi-resident protein whose stem region is not required for its enzymatic activity but is responsible for its intracellular localization (41). However, it is not yet known whether this is also valid for XT-II, and we will have to investigate this after identification of the enzymatic function of this protein.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Similar results have been reported for GnT-V, a Golgi-resident protein whose stem region is not required for its enzymatic activity but is responsible for its intracellular localization (41). However, it is not yet known whether this is also valid for XT-II, and we will have to investigate this after identification of the enzymatic function of this protein.…”
Section: Discussionsupporting
confidence: 48%
“…The way in which our XT-I and XT-II data can be reconciled with the kin recognition theory should be investigated in further studies. The present investigations reported that for some glycoyltransferases, oligomerization of the stem region was responsible for their Golgi retention (41), whereas others still showed Golgi retention after the disruption of the protein-protein interactions (42,43). We could only hypothesize that the truncated stem region of XT-I leads to decreased formation of aggregates and therefore to impaired Golgi retention.…”
Section: Discussionmentioning
confidence: 75%
“…Neither model completely explains the observations in the literature. The stem region or cytoplasmic tail also may influence Golgi retention of some glycosyltransferases (Milland et al, 2001;Sasai et al, 2001). In any case, the Golgi retention mechanism must be altered or overridden for GalT-I to move to the plasma membrane.…”
Section: B Receptors For Zona Pellucida Proteinsmentioning
confidence: 99%
“…Because deletion mutants, which contain CTS regions alone, could be localized at the Golgi apparatus (31)(32)(33), the CTS regions function as Golgi retention signals for various glycosyltransferases (34). Furthermore, because the substitution of CTS regions for those of other glycosyltransferases resulted in different ultimate oligosaccharide structures because of an alteration in subcompartment distribution (8), the CTS regions of glycosyltransferases play important roles as intrinsic signals for regulating their distribution in the Golgi subcompartment.…”
Section: Discussionmentioning
confidence: 99%